An idea to reduce angular dependence of dosimeter having a disk-shaped detection region. (September 2020) - Goto, Sota; Hayashi, Hiroaki; Asahara, Takashi; Kimoto, Natsumi; Tomita, Emi; Takegami, Kazuki; Asakawa, Takumi; Kanazawa, Yuki; Okazaki, Tohru; Hashizume, Takuya
Abstract: When dose measurement is carried out using an optically stimulated luminescence (OSL) dosimeter having a disk-shaped sensitivity element during diagnostic X-ray examination, the angular dependence of the dosimeter should be taken into consideration. Angular dependence is the characteristic in which the detector response varies depending on the incident angle of X-rays to the dosimeter. This becomes one of the causes of systematic uncertainty. In order to measure an exposure dose accurately, it is important to reduce the uncertainty component of angular dependence. In this study, we propose two types of novel disk-shaped dosimeters for trials to reduce angular dependence; one is an annular disk-shaped dosimeter, and the other is a composite-disk-shaped dosimeter. Because the disk-shaped detection region, which is composed of Al2 O3 :C, is used in a commercially available dosimeter, we fabricate our novel dosimeters based on these materials. The annular disk-shaped dosimeter is a ϕ5 mm disk having a ϕ3 mm hole in it. The other is a composite-disk-shaped dosimeter which has two sensitive regions; an inverted ϕ3 mm disk detection region is inserted into the annular disk-shaped dosimeter. We performed Monte-Carlo simulation and an experiment using 40–140 kV X-rays to evaluate the angular dependence and detection efficiencies of these dosimeters. For the simulation, incident angles of X-rays to the dosimeter varied from 0°– 345° at every 15°. The experiment was performed under the same conditions. We focused our attention on the difference of the angular dependence between 0° and 90°, and the ratio of responses at 90° divided by 0° was evaluated; the results of ratios for the disk-shaped dosimeter, annular disk-shaped dosimeter, and composite disk-shaped dosimeter were 78%, 85%, and 83%, respectively. The relative detection efficiencies of the disk-shaped dosimeter, annular disk-shaped dosimeter, and composite disk-shaped dosimeter were 100%, 64%, and 100%, respectively. Based on these results, we concluded that the composite disk-shaped dosimeter can accomplish better angular dependence without loss of sensitivity. The characteristics of the conventionally-used disk-shaped dosimeter can be improved by altering the shape. Highlights: An idea for improving angular dependence is proposed. Novel-shaped OSL dosimeters have been developed. Angular dependence is evaluated by simulations and experiments.